Konsep Dan Teori Good Corporate Governance Pada PT. Bank Syariah Indonesia - Muhammad Iqbal; Erlina Erlina; Fadhila Audi Ubay; Muhammad Alwan Atha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research discusses the concepts and theories of good corporate governance applied at PT. Indonesian Sharia Bank. This article reviews the importance of implementing the principles of good corporate governance in the sharia banking industry, with a focus on PT. Indonesian Sharia Bank. In this article, the author explains the concepts and theories of good corporate governance and their relevance to PT. Indonesian Sharia Bank. The author also discusses how PT. Bank Syariah Indonesia applies the principles of good corporate governance in its operations. This article also reviews the benefits obtained by PT. Bank Syariah Indonesia through the implementation of good corporate governance. In this research, the author used a descriptive-analytical method by collecting data through literature studies and analysis of PT's corporate governance policies and practices. Indonesian Sharia Bank. The research results show that the implementation of good corporate governance at PT. Bank Syariah Indonesia has had a positive impact on company performance and the trust of shareholders and customers. The conclusion of this article discusses the concepts and theories of good corporate governance and their application at PT. Indonesian Sharia Bank.Implementation of good corporate governance at PT. Bank Syariah Indonesia provides benefits in improving company performance and shareholder and customer trust.